Synthesis of Solution-Processed Cu2ZnSnSe4 Thin Films on Transparent Conducting Oxide Glass Substrates - Ismail, Agus; Cho, Jin Woo; Park, Se Jin; Hwang, Yun Jeong; Min, Byoung Koun (KOREAN CHEMICAL SOC, 2014)
Cu2ZnSnSe4 (CZTSe) thin films were synthesized on transparent conducting oxide glass substrates via a simple, non-toxic, and low-cost process using a precursor solution paste. A three-step heating process (oxidation, sulfurization, and selenization) was employed to synthesize a CZTSe thin film as an absorber layer for use in thin-film solar cells. In particular, we focused on the effects of sulfurization conditions on CZTSe film formation. We found that sulfurization at 400 degrees C involves the formation of secondary phases such as CuSe2 and Cu2SnSe3, but they gradually disappeared when the temperature was increased. The formed CZTSe thin films showed homogenous and good crystallinity with grain sizes of approximately 600 nm. A solar cell device was tentatively fabricated and showed a power conversion efficiency of 2.2% on an active area of 0.44 cm(2) with an open circuit voltage of 365 mV, a short current density of 20.6 mA/cm(2), and a fill factor of 28.7%.
Keywords: SOLAR-CELLS; PRECURSORS; GROWTH